An evaluation of the outcome of bull castration by intra-testicular injection of ethartol and calcium chloride - Canpolat, I.; Gur, S.; Gunay, C.; Bulut, S.; Eroksuz, H. (My University, 2006)
In this study, the effectiveness of intra-testicular ethanol and calcium chloride administrations was compared for chemical-castration in 12 mix-bred young bulls (12-15 months old and 250-400 kg). Ten ml of absolute ethanol or 10 ml of a 30 % calcium chloride solution were administered intra-testicularly in each testicle which were removed with the open surgical technique after 60 days for histopathologic evaluation. Testicular swelling was evident in both group bulls following injection and reached peak within 48 hours. While testicular volume decreased significantly in ethanol group after 3 weeks, no significant change occurred in calcium chloride group. The testicles underwent atrophy at the 60th day in ethanol group with no marked alteration in calcium chloride group. Semen characteristics of only 3 bulls in ethanol group were very poor. Though only 3 bulls were infertile in ethanol injected group, other bulls were fertile. The method is readily applicable with no major harms and adverse effects. If 50 % rate is considered satisfactory it can be used then in large flocks, in particularly where no chance of operation exists.
Keywords: Bull; Calcium chloride; Chemo sterilization; Ethanol